FUNCTIONAL METHODS OF RESTORATIVE TREATMENT OF PATIENTS WITH POSTTRAUMATIC CONTRACTURES OF THE ELBOW JOINT - Akhtamov A; Akhtamov A.A (Western European Studies, 2024)
The results of treatment of 36 patients with posttraumatic contractures of the elbow joint are presented, among them, 17 patients had restrictions on both flexion and extensor movements, so is the pronacin-supination function of the forearm. After a complex of restorative measures in the elbow joint, good functional results were obtained in 29 (80.6%) patients, satisfactory in 2 (5.5%), unsatisfactory in 5 (13.9%) patients
Keywords: elbow joint; contracture; physical therapy